Development of Multiple-Choice Based on Automatic Assessment through Quizizz Respiratory System Material in Humans - Lavina Azza Khaerina; Aldina Eka Andriani (Jurnal Pijar MIPA, 2026)
Teachers have not been effective in presenting learning evaluations, using a variety of stimuli and question types, resulting in delays in delivering feedback to students. This study aims to describe the development design, test the feasibility, and test the effectiveness of multiple-choice questions based on automatic assessment via Quizizz, using respiratory system material in class V SD N Sekaran 01, Semarang City. The research conducted is R&D (Research and Development) and the ADDIE (analysis, design, development, implementation, Evaluation) development model. The data collection technique uses both tests and non-tests. Data analysis techniques included normality testing, t-tests, and N-Gain. The results of this study include the design of a multiple-choice development based on automatic assessment through Quizizz, with the following question types: standard multiple choice, complex multiple choice, and two-tier multiple choice. Each question is accompanied by a varied, context-specific stimulus in the form of videos, images, tables, and narrative text. The feasibility of multiple-choice automatic assessment via a questionnaire on respiratory system material in humans was demonstrated, with material experts achieving 92.85% and media experts achieving 89.28%, both within very feasible criteria. The effectiveness of multiple-choice questions based on automatic assessment through Quizizz showed an increase in pre-test and post-test by 28.08. The Paired Sample t-test yielded a p-value of 0.00, indicating a significant difference in student learning outcomes, which is supported by the N-Gain test, which yielded 0.5687 with moderate criteria. Thus, a multiple-choice assessment based on Automatic Assessment through Quizizz has been successfully developed, is feasible, and effective in improving students' learning outcomes in grade V at SD N Sekaran 01, Semarang City.